Growth and behaviour of blue mussels, a re-emerging polar resident, follow a strong annual rhythm shaped by the extreme high Arctic light regime. Issue 10 (14th October 2020) - Tran, Damien; Andrade, Hector; Durier, Guillaume; Ciret, Pierre; Leopold, Peter; Sow, Mohamedou; Ballantine, Carl; Camus, Lionel; Berge, Jørgen; Perrigault, Mickael
Abstract : Polar regions are currently warming at a rate above the global average. One issue of concern is the consequences on biodiversity in relation to the Northward latitudinal shift in distribution of temperate species. In the present study, lasting almost two years, we examined two phenological traits, i.e. the shell growth and behavioural rhythm of a recently re-established species in the high Arctic, the blue mussel Mytilus sp. We compared this with a native species, the Islandic scallop Chlamys islandica . We show marked differences in the examined traits between the two species. In Mytilus sp., a clear annual pattern of shell growth strongly correlated to the valve behaviour rhythmicity, whereas C. islandica exhibited a shell growth pattern with a total absence of annual rhythmicity of behaviour. The shell growth was highly correlated to the photoperiod for the mussels but weaker for the scallops. The water temperature cycle was a very weak parameter to anticipate the phenology traits of both species. This study shows that the new resident in the high Arctic, Mytilus sp., is a highly adaptive species, and therefore a promising bioindicator to study the consequences of biodiversity changes due to global warming.